Perlindungan Hak Kekayaan Intelektual Terhadap Perbatikan (Tinjauan Terhadap Batik Yogyakarta Dan Solo) - Euis Sunaryo (JIPRO: Journal of Intellectual Property, 2019)
One of the traditional knowledges in the arts and culture that is protected by Indonesia is Batik. Traditional batik with its classic motifs has been worked on for generations and is included in Traditional Knowledge and Traditional Cultural Expressions. Not all batik is registered for copyright because batik that needs copyright protection under Article 11 paragraph (1) letter f of the 1987 Copyright Act is a new art of batik. The problem that arises is how the legal protection of Yogyakarta Batik and Solo Batik is applied as Traditional Knowledge and Intellectual Property Rights (IPR). The purpose of this research is to know and understand the legal protection that can be obtained by Batik Yogyakarta and Batik Solo as the application of Traditional Knowledge and Intellectual Property Rights (IPR). The main theory used in this thesis research is John Locke's theory of Natural Law which states that the concept of property has something to do with human rights with its statement 'life, liberty, property'. The research method used is empirical normative research with qualitative research carried out in the field (field research) and take a research method with a non-judicial case study approach. The conclusion of the research is legal protection for Batik Yogyakarta and Solo as Traditional Knowledge carried out by the State by inventorying traditional batik motifs and maintaining Traditional Knowledge and Traditional Cultural Expressions.The legal protection of Intellectual Property Rights (IPR) that can be applied to Yogyakarta and Solo Batik is through the Copyright, Trademark, Patent and Trade Secret regimes.